2014
DOI: 10.1517/17425247.2014.944861
|View full text |Cite
|
Sign up to set email alerts
|

Formulation optimization of gastroretentive drug delivery system for allopurinol using experimental design

Abstract: Introduction: The objective of the present investigation was to develop a multiparticulate modified release system of methylphenidate hydrochloride (HCl) generating biphasic release profile from single core. Materials and Methods: Wurster (bottom spray fluid bed coating) process was employed to develop extended release (ER) pellets of methylphenidate HCl. Impact of various formulation variables was assessed using statistical interpretation such as analysis of variance. A 3 2 (two factor, three level) factorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…However, the effect of the polymer Badam gum was more pronounced than HPMC K4 M on bioadhesion strength since Badam gum has significant sticking property these findings are in agreement with previously reported results by Meka, et al, [23] who found the Badam gum has remarkable swelling and sticking character in gastric pH. [23][24][25][26][27][28][29][30][31][32][33] This developed floating-bioadhesive combination formulation would overcome the drawback of floating and bioadhesive individual system and improving the therapeutic effect of the drug involved.…”
Section: Bioadhesive Strengthsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the effect of the polymer Badam gum was more pronounced than HPMC K4 M on bioadhesion strength since Badam gum has significant sticking property these findings are in agreement with previously reported results by Meka, et al, [23] who found the Badam gum has remarkable swelling and sticking character in gastric pH. [23][24][25][26][27][28][29][30][31][32][33] This developed floating-bioadhesive combination formulation would overcome the drawback of floating and bioadhesive individual system and improving the therapeutic effect of the drug involved.…”
Section: Bioadhesive Strengthsupporting
confidence: 90%
“…Floating lag time and total floating duration (time during which tablet remains buoyant) were recorded. [25] In vitro drug release studies Drug release studies of the prepared floating bioadhesive tablets were performed, in triplicate, in a USP dissolution tester apparatus, type-II (Paddle method) (dissolution tester, electro lab) at 37 ± 0.50°C. The paddles rotated at a speed of 50 rpm.…”
Section: Si Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Gastro-retentive systems are usually appropriate for drugs having certain properties/limitations like local action, good absorption from stomach, poor aqueous solubility, unstability at alkaline pH and/or narrow absorption window 1,[5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Drug Dev Ind Pharm, Early Online:[1][2][3][4][5][6][7] Drug Dev Ind Pharm Downloaded from informahealthcare.com by Yale Dermatologic Surgery on 07/08/15For personal use only.…”
mentioning
confidence: 99%